Effects of a Single Session of High- and Moderate-Intensity Resistance Exercise on Endothelial Function of Middle-Aged Sedentary Men - Boeno, Francesco Pinto; Farinha, Juliano Boufleur; Ramis, Thiago Rozales; Macedo, Rodrigo Cauduro Oliveira; Rodrigues-Krause, Josianne; do Nascimento Queiroz, Jessica; Lopez, Pedro; Pinto, Ronei Silveira; Reischak-Oliveira, Alvaro (Frontiers in Physiology, 2019)
Regular resistance exercise is associated with metabolic, neuromuscular and cardiovascular adaptations which improve quality of life and health. However, sedentary subjects have shown acute impairments in endothelial function after high-intensity resistance exercise. The aim of this study was to evaluate endothelial function in sedentary middle-aged men after a single session of resistance exercise at different intensities. Eleven sedentary middle-aged men (40.1±3.9 years; 27.3±1.4 kg/m2) underwent three different conditions of assessment: 1) single knee extension exercise at moderate intensity (MI) [4 sets of 12 repetitions at 50% of one repetition maximal (1RM) for each leg], 2) single knee extension exercise at high intensity (HI) (4 sets of 8 repetitions at 80% of 1RM for each leg), 3) resting for the control condition (CON). Flow-mediated dilation (FMD) was assessed before, 30 and 60 min after exercise. Plasma concentrations of endothelin-1 (ET-1), nitrites and nitrates (NOx) and thiobarbituric acid reactive substances (TBARS) were measured before, immediately after and 60 min after exercise. Blood pressure (BP) was measured prior to the experimental protocols, and in the following times: immediately following, and 2, 5, 10, 15, 30 and 60 min after exertion. There was a significant improvement in FMD 30 min after MI condition (12.5±4.10 vs 17.2±3.9%; p=0.016). NOx levels were significantly higher immediately after MI (6.8±3.3 vs. 12.6±4.2 μM; p=0.007) and there was a significant increase in the concentration of ET-1 immediately after HI (20.02±2.2 vs. 25.4±2.1 pg/mL; p=0.004). However, there was no significant difference for BP (MI vs. HI) and TBARS among the experimental conditions. Resistance exercise performed at moderate intensity improved vasodilatation via increases on NOx levels and FMD in sedentary middle-aged men.